2010
DOI: 10.1007/s12010-010-9032-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Biosurfactant-Producing Indigenous Microorganisms that Enhance Residue Oil Recovery in an Oil Reservoir After Polymer Flooding

Abstract: Three biosurfactant-producing indigenous microorganisms (XDS1, XDS2, XDS3) were isolated from a petroleum reservoir in the Daqing Oilfield (China) after polymer flooding. Their metabolic, biochemical, and oil-degradation characteristics, as well as their oil displacement in the core were studied. These indigenous microorganisms were identified as short rod bacillus bacteria with white color, round shape, a protruding structure, and a rough surface. Strains have peritrichous flagella, are able to produce endosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 19 publications
1
39
0
Order By: Relevance
“…The most abundant compound present during the ninth day of incubation was hexadecanoic acid (RT 14.87) for B. firmus and dodecane (RT 12.42) for B. halodurans (Tables 2 and 3). Bacteria from the oil fields in Japan and China degrading n-alkane were reported [33,61]. B. firmus and B. halodurans in this study showed fractionation of higher n-alkanes having carbon numbers up to C 54 .…”
Section: Discussionmentioning
confidence: 52%
“…The most abundant compound present during the ninth day of incubation was hexadecanoic acid (RT 14.87) for B. firmus and dodecane (RT 12.42) for B. halodurans (Tables 2 and 3). Bacteria from the oil fields in Japan and China degrading n-alkane were reported [33,61]. B. firmus and B. halodurans in this study showed fractionation of higher n-alkanes having carbon numbers up to C 54 .…”
Section: Discussionmentioning
confidence: 52%
“…It is known that HDB release surfactants or emulsifiers in order to facilitate assimilation of insoluble substrates such as crude oil (Bucheli-Witschel and Egli 2010); indeed, biosurfactants are structurally diverse amphiphiles that are secreted in the environment to facilitate the diffusion and uptake by microorganisms of hydrophobic substances from aqueous media (Lawniczak et al 2013). Biosurfactant-producing microbes are found in various ecosystems, especially in those polluted with hydrophobic contaminants, such as petroleum wastes which are more yielding than undisturbed environments (Belcher et al 2012;She et al 2011). The bioavailability of petroleum products to microorganisms of oil-degrading community is considerably affected by biosurfactants, which isolate individual petroleum molecules in micelles (Belcher et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The surface tension and viscosity of the crude oil decreased after being treated by the three strains of microorganisms. The core-flooding tests showed that the incremental oil recoveries ranged from 4.89% to 6.96% ( She, 2011). The biosurfactant production of two surfactant producing bacteria HD-322-2 and T103 is 321mg/L, and 195mg/L, respectively.…”
Section: Othersmentioning
confidence: 99%